Medicinal Plants Used as Snake Venom Antidotes in East African Community: Review and Assessment of Scientific Evidences - Omara, Timothy; Kiwanuka Nakiguli, Caroline; Naiyl, Rania Awad; Atieno Opondo, Florence; Otieno, Sadia Benard; Ndiege, Merab Lilian; Mbabazi, Immaculate; Nassazi, Winfred; Nteziyaremye, Papias; Kagoya, Sarah; Okwir, Augastine; Etimu, Edmond (Journal of Medicinal and Chemical Sciences, 2021)
Poisonous snake envenomation is a complex neglected health problem implicated in mortality, disability, psychological morbidity, and socio-economic losses recorded worldwide. An antivenin serum, the only medically recommended treatment for snakebites, has several drawbacks including, hypersensitivity, inability to prevent local tissue damage, are scarce and unaffordable in most snakebite endemic areas. In many rural communities all over the world, plants have been utilized for managing snakebites. This review seeks to identify plants reported as antivenom remedies in the East Africa and the scientific studies thereof which could support their use in the treatment of snake envenomation. A review of scientific articles was undertaken to identify information on traditional knowledge of medicinal plants used to treat snake envenomation in East Africa and their antivenom efficacy. A total of 361 plant species were retrieved to have been reported as traditional therapies for snakebites in East Africa. The review identified distinct cases of doctrine of signatures and zoopharmacognosy in snakes using Opilia amentacea, Hugonia castaneifolia and Microglossa pyrifolia respectively. Evaluations of the antivenom efficacy of 44 species (12.2%) have been done globally, and most species found to be effective in neutralizing the lethal activities of snake venoms. Ethnomedicinal plants play a revered holistic role in East African antisnake venom therapy. Conyza sumatrensis, Hyptis pectinata, Justicia betonica, and Maesa lanceolata used to treat specific snakebites merit further studies.
Keywords: Antivenom plants; Neglected tropical disease; Snakebites; Sub-Saharan Africa; Traditional medicine